Prolonged survival and decreased abnormal movements in transgenic model of Huntington disease, with administration of the transglutaminase inhibitor cystamine - Karpuj, Marcela V.; Becher, Mark W.; Springer, Joe E.; Chabas, Dorothee; Youssef, Sawsan; Pedotti, Rosetta; Mitchell, Dennis; Steinman, Lawrence (Nature medicine, 2002)
An expanded polyglutamine domain in huntingtin underlies the pathogenic events in Huntington disease (HD), characterized by chorea, dementia and severe weight loss, culminating in death. Transglutaminase (TGase) may be critical in the pathogenesis, via cross-linking huntingtin. Administration of the TGase competitive inhibitor, cystamine, to transgenic mice expressing exon 1 of huntingtin containing an expanded polyglutamine repeat, altered the course of their HD-like disease. Cystamine given intraperitoneally entered brain where it inhibited TGase activity. When treatment began after the appearance of abnormal movements, cystamine extended survival, reduced associated tremor and abnormal movements and ameliorated weight loss. Treatment did not influence the appearance or frequency of neuronal nuclear inclusions. Unexpectedly, cystamine treatment increased transcription of one of the two genes shown to be neuroprotective for polyglutamine toxicity in Drosophila , dnaj (also known as HDJ1 and Hsp40 in humans and mice, respectively). Inhibition of TGase provides a new treatment strategy for HD and other polyglutamine diseases.